Mutational screening in the LDLR gene among patients presenting familial hypercholesterolemia in the Southeast of Brazil - Molfetta, Greice Andreotti (2017)
Zanette, Dalila Lucíola. “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.